Sputtered Al2O3 coatings and its effect on protection of nitride coatings - Yan, Shan Shan (2015)
Nitride hard coatings are of high hardness and excellent wear resistance but low oxidation resistance and low hot hardness, which limit their working temperature below 900°C. Aluminum oxide coatings (Al2O3) perform well as hard coating in wear & oxidation protection due to high hot hardness, chemical durability, oxidation resistant and stability at elevated temperature. However, poor adhesion of deposited Al2O3 coatings on stainless steel substrate in my own research was observed. Therefore the potential solution is to apply Al2O3 coating on top of nitride-based coating to improve the hot hardness and oxidation resistance of nitride coatings. This project aims to develop Al2O3 coating by reactive magnetron sputtering system, whereby to study the influence of deposition parameters on microstructure and mechanical properties. It also investigates the annealing effect of aluminum oxide coatings on microstructure and mechanical properties as well as the effect of aluminum oxide coatings on protection of nitride coating. The Al2O3 coatings were deposited on stainless steel with pre-coated CrAlSiN by reactive magnetron sputtering in an argon-oxygen atmosphere. The heat treatment was done in ambient atmosphere for 1 hour with different annealing temperatures. Grazing incidence X-ray diffraction and scanning electron microscope were employed to characterize the microstructures and morphology. Nanoindentation and Rockwell indentation were used in characterization of the hardness and adhesion. The hardness and O, N content of CrAlSiN coating with/without oxide layer were examined to characterize the oxidation protection effect. It is found that the as-deposited aluminum oxide coatings are amorphous. The O2 flow rate plays a critical role for the microstructure and mechanical properties. The optimized O2/Ar flow rate ratio is 1:7.5. Microstructural and mechanical properties changes are observed upon thermal annealing. The amorphous coatings were converted to crystalline γ-Al2O3 and α-Al2O3 after high temperature annealing, above 700°C. The coating hardness increases with annealing temperature increases due to the structure transition from amorphous to crystalline. No O content and only a minor hardness reduction were observed for the CrAlSiN with Al2O3 top protection layer, while serious oxidation and hardness degradation occur for the bare CrAlSiN samples.